Językowy obraz świata we współczesnej niemieckiej literaturze kryminalnej na podstawie wybranych kolokacji i okazjonalizmów - implikacje dydaktyczne = Linguistic picture of the world in contemporary german literature of crime on the basis of selected collocation and occasionally used phrases - educational implications - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article the author analyzes an example of a German criminal story, which can be used as teaching material for classes "German as a foreign language". Taking into account the concept of linguistic picture of the world (językowy obraz świata) the author shows that collocations and occasionally used phrases, included in the contemporary crime fiction, are a valuable source of knowledge not only about the realities of the modern world, but they can expand the lexical base by students interested in this type of literature.
Keywords: literatura niemiecka - tematyka - 21 w.; powieść kryminalna